2018
DOI: 10.1007/s10840-018-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

N-3 polyunsaturated fatty acids for prevention of postoperative atrial fibrillation: updated meta-analysis and systematic review

Abstract: PUFA appears to reduce the incidence of POAF. However, the said protective effect may be influenced by EPA/DHA ratio, with < 1 appearing preferable. PUFA efficacy on POAF prevention appeared insignificant when compared with non-fish oils and only apparent in the setting of CABG alone. Further studies are needed to confirm the effect of PUFA on POAF and to assess the proper use of PUFA against POAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
0
13
0
8
Order By: Relevance
“…Early trials have not shown a reduction in AFACS [113], and a 2014 meta-analysis of 8 RCTs ( n = 2687) concluded that preoperative PUFA treatment did not influence AFACS incidence [86]. In 2017, a meta-analysis of 19 RCTs ( n = 4335) found a reduction in AFACS [87], and so did a 2018 meta-analysis that included 14 RCTs ( n = 3570), which found significant AFACS reduction with PUFA vs controls (OR 0.84, 95% CI 0.71–0.99, p = 0.03), although this effect was found only in CABG and not valve surgery [88]. This appears to be a promising intervention for AF prophylaxis, which may incur few risks from adverse effects and costs, but has not been addressed by any guidelines to date.…”
Section: Preventative Strategies and Associated Evidence Basementioning
confidence: 99%
“…Early trials have not shown a reduction in AFACS [113], and a 2014 meta-analysis of 8 RCTs ( n = 2687) concluded that preoperative PUFA treatment did not influence AFACS incidence [86]. In 2017, a meta-analysis of 19 RCTs ( n = 4335) found a reduction in AFACS [87], and so did a 2018 meta-analysis that included 14 RCTs ( n = 3570), which found significant AFACS reduction with PUFA vs controls (OR 0.84, 95% CI 0.71–0.99, p = 0.03), although this effect was found only in CABG and not valve surgery [88]. This appears to be a promising intervention for AF prophylaxis, which may incur few risks from adverse effects and costs, but has not been addressed by any guidelines to date.…”
Section: Preventative Strategies and Associated Evidence Basementioning
confidence: 99%
“…Omega-3 fatty acids (Omega-3s) are long-chain, polyunsaturated fatty acids, which include eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), mainly obtained from fish 45 . There is evidence on the usefulness of omega-3s supplementation in cardiovascular mortality, myocardial ischemia, and AFACS.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…In the subgroup analysis, the incidence of PAF was lower in patients who received omega-3s whose EPA/DHA composition was lower than 1 and in patients with revascularization procedures. The number needed to treat was 25 45 . From the authors' point of view, omega-3 fatty acids are part of the third-line prophylactic treatment for the prevention of AFACS.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…In the last decade, ω-3 PUFA have become an important ally in postoperative inflammation and metabolic control in cardiovascular surgery, as it is directly related to a reduction in proinflammatory cytokines and incidence of postoperative arrhythmia, particularly postoperative atrial fibrillation. The protective effects of this type of fish oil have also been observed in critically ill patients in the intensive care unit, usually in parenteral nutrition regimens [5,6] .…”
mentioning
confidence: 99%
“…Results showed that perioperative infusions significantly increased the concentration of ω-3 PUFA in platelet membrane and atrial tissue within 12 hours of the first infusion and significantly lowered clinical and biological signs of inflammation. In a recent meta-analysis (14 studies) on the use of ω-3 PUFA, Wang et al [6] showed promising results, with a lower incidence of POAF (RR 0.84 [95% CI 0.73-0.98], P =0.03). These results, however, were only for coronary artery bypass grafting (0.68 [0.47-0.97], P =0.03); none of the other types of surgery analyzed showed similar results.…”
mentioning
confidence: 99%